2020
DOI: 10.1136/gutjnl-2020-322980
|View full text |Cite
|
Sign up to set email alerts
|

NAIL: an evolutionarily conserved lncRNA essential for licensing coordinated activation of p38 and NFκB in colitis

Abstract: ObjectiveNFκB is the key modulator in inflammatory disorders. However, the key regulators that activate, fine-tune or shut off NFκB activity in inflammatory conditions are poorly understood. In this study, we aim to investigate the roles that NFκB-specific long non-coding RNAs (lncRNAs) play in regulating inflammatory networks.DesignUsing the first genetic-screen to identify NFκB-specific lncRNAs, we performed RNA-seq from the p65-/- and Ikkβ-/- mouse embryonic fibroblasts and report the identification of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…These proinflammatory and immunomodulatory mediators secreted by MCs contribute to host immunity and different diseases including but not limited to psoriasis, myalgic encephalomyelitis/chronic fatigue syndrome, interstitial cystitis, autism spectrum disorders, multiple sclerosis, rheumatoid arthritis, cancer, cardiovascular diseases, and other inflammation-related diseases besides allergy that can recognize pathogens. 33,58 These properties provide MCs with advantages to very rapidly act as sentinels to guard against a plethora of invading pathogens. This role of MCs in defense against invading pathogens was first reported in the context of parasitic infections.…”
Section: Role Of Mcs In Infectious Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…These proinflammatory and immunomodulatory mediators secreted by MCs contribute to host immunity and different diseases including but not limited to psoriasis, myalgic encephalomyelitis/chronic fatigue syndrome, interstitial cystitis, autism spectrum disorders, multiple sclerosis, rheumatoid arthritis, cancer, cardiovascular diseases, and other inflammation-related diseases besides allergy that can recognize pathogens. 33,58 These properties provide MCs with advantages to very rapidly act as sentinels to guard against a plethora of invading pathogens. This role of MCs in defense against invading pathogens was first reported in the context of parasitic infections.…”
Section: Role Of Mcs In Infectious Diseasesmentioning
confidence: 99%
“… 1 , 2 , 17 , 22 , 26 , 27 , 28 , 29 , 30 Hours later, numerous de novo synthesized cytokines and chemokines are also released from activated MCs as effectors of their functions. 1 , 2 , 17 , 22 , 23 , 25 , 31 , 32 , 33 , 34 Due to their distribution and expression of numerous arrays of membrane receptors, as well as the broad spectrum of inflammatory mediators they produce, 22 , 35 , 36 , 37 MCs can act as the first‐line responders in host defense against a number of pathogens and have long been recognized for their key effector role in allergic inflammation. However, recently there is evidence that MCs may be playing a key role in the pathogenesis of coronavirus/COVID‐19 disease.…”
Section: Mast Cell Genesis and Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the key regulators that activate, fine-tune, or turn off NFκB activity under inflammatory conditions. Akıncılar et al [103] designed the first genetic screening method to identify the specific lncRNA of NFκB and found a conservative lncRNA named NAIL. After a series of experiments, the authors found that NAIL can cooperate with another inflammatory factor, P38, to activate NF-κB and induce progenitor cells to differentiate into immature myeloid cells in the bone marrow, macrophages reassemble to the inflammatory region, and express inflammatory genes in colitis.…”
Section: Lncrna As a Potential Therapeutic Target For Inflammatorymentioning
confidence: 99%
“…PTENP1 can exert a growth-suppressive role by regulating cellular levels of PTEN [ 6 ]. NAIL identified in colitis patients that regulates inflammation through NFkB which is important for the inflammation [ 7 ], and cross-talk of NFkB and HIF signaling pathways in mediating the occurrence of inflammation. LncRNA PTTG3P (pituitary tumor-transforming 3, pseudogene, NR_002734), located at chromosome 8q13.1, was first reported in the study of the human pituitary tumor transforming gene ( hPTTG ) family in 2000 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%